Differential activation of amygdala, dorsal and ventral hippocampus following an exposure to a reminder of underwater trauma - Ritov, Gilad; Ardi, Ziv; Richter-Levin, Gal (Frontiers in Behavioral Neuroscience, 2014)
Recollection of emotional memories is attributed in part to the activation of the amygdala and the hippocampus. Recent hypothesis suggest a pivotal role for the ventral hippocampus in traumatic stress processing and emotional memory retrieval. Persistent re-experiencing and intrusive recollections are core symptoms in acute and posttraumatic stress disorders (ASD; PTSD). Such intrusive recollections are often triggered by reminders associated with the trauma. We examined the impact of exposure to a trauma reminder (under water trauma) on the activation of the basolateral amygdala (BLA), dorsal and ventral hippocampus. Rats were exposed to underwater trauma and 24 hours later were re-exposed to the context of the trauma. Phosphorylation of the extracellular signal-regulated kinase (ERK) was used as a marker for level of activation of these regions. Significant increase in ERK activation was found in the ventral hippocampus and BLA. Such pattern of activation was not found in animals exposed only to the trauma or in animals exposed only to the trauma reminder. Additionally, the dissociative pattern of activation of the ventral hippocampus sub-regions positively correlated with the activation of the BLA. Our findings suggest a specific pattern of neural activation during recollection of a trauma reminder, with a unique contribution of the ventral hippocampus. Measured 24 hrs after the exposure to the traumatic experience, the current findings relate to relatively early stages of traumatic memory consolidation. Understanding the neural mechanisms underlying these initial stages may contribute to developing intervention strategies that could reduce the risk of eventually developing PTSD.